Synthesis and characterization of Schiff's base-based chemosensor and its detection potential of Fluoride ions. Issue 1 (July 2021) - Kurniawan, C; Wati, R R; Prasetya, A T; Priatmoko, S; Kasmui, K; Bahron, H
Abstract: The development of selective and sensitive chemical sensors to overcome fluoride ions is needed, especially for applications in chemical and biological processes. One of the chemical compounds that can act as sensors is the Schiff base compound group. This study aims to synthesis a Schiff base based on salicylaldehyde and as a fluoride ion sensor. The one-pot synthesis approach was carried out in room terms by mixing salicylaldehyde with hydrazine hydrate or phenylenediamine with a molar ratio of 2: 1 in ethanol solvent under stirring for 24 hours. The bright yellow crystal was obtained with a yield of 80% for salicylaldazine (SB). The compounds in the dimethyl sulfoxide (DMSO) solvent tend to be colorless, but in the presence of F-ions, the solution turns orange. The results indicate an interaction between SB1 with F-ions in solution.